2016
DOI: 10.1038/srep18531
|View full text |Cite
|
Sign up to set email alerts
|

Electrical current through individual pairs of phosphorus donor atoms and silicon dangling bonds

Abstract: Nuclear spins of phosphorus [P] donor atoms in crystalline silicon are among the most coherent qubits found in nature. For their utilization in scalable quantum computers, distinct donor electron wavefunctions must be controlled and probed through electrical coupling by application of either highly localized electric fields or spin-selective currents. Due to the strong modulation of the P-donor wavefunction by the silicon lattice, such electrical coupling requires atomic spatial accuracy. Here, the spatially c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…In contrast to larger CPs, the smallest CPs that we have observed can be fitted by Gaussian distributions and they typically show diameters with a full width at half maximum (FWHM) of ~1 nm as shown in Figure 1d. We therefore conclude that these features in the cAFM measurements are not governed by the resolution of our setup, which is about 5 Å as determined for Pb centers located at the c-Si/SiO2 interfaces 39 .…”
Section: Current Variations On the Nanometer Scalesupporting
confidence: 57%
See 1 more Smart Citation
“…In contrast to larger CPs, the smallest CPs that we have observed can be fitted by Gaussian distributions and they typically show diameters with a full width at half maximum (FWHM) of ~1 nm as shown in Figure 1d. We therefore conclude that these features in the cAFM measurements are not governed by the resolution of our setup, which is about 5 Å as determined for Pb centers located at the c-Si/SiO2 interfaces 39 .…”
Section: Current Variations On the Nanometer Scalesupporting
confidence: 57%
“…3e of the main text was, under the given conditions, qualitatively reproduced at about one quarter of the CPs where this experiment was repeated, yet this alone does not proof that this effect is not an artifact, e.g. due to weakly bond surface atoms which swtich their location randomly between the tip and the surface 38,39 . To test these observations for such artifacts, we identified first the a location of a pronounced CP which displayed RTN [see blue circled area in Figure S9a] and then a location within a HA were no RTN was seen [see red circled area in Figure S9a].…”
Section: Exclusion Of Artifact Signals For Random Telegraph Noise (Rt...mentioning
confidence: 87%
“…This state spreads over several atomic rows with a width of about 2 nm in real space. It is much wider than the trivial edge state induced by edge dangling bonds or atomic reconstructions, which decays exponentially away from the terrace edge (25,26). Indeed, there is a clear dangling-induced state along the terrace edge with a spatial distribution of less than 1 nm (Figure 3f).…”
Section: Main Textmentioning
confidence: 95%
“…It was recently shown that EDMR in Si:P is primarily sensitive to those donors located within roughly the first 20 nm of the Si/SiO 2 surface [34]. The properties of a single donor-defect pair were also recently characterized using scanning probe techniques [35]. Figure 2(a) shows a schematic of the experimental setup used.…”
Section: Spin Dependent Recombinationmentioning
confidence: 99%